Quantum chemical analysis of harmful dye 3-[ (4-anilinophenyl) diazenyl] benzenesulfonate, metanil yellow - Parbat, Shreyas (International Journal of Advanced Chemistry, 2020)
In the present work, quantum chemical study of the harmful dye, metanil yellow is conducted. The optimized molecular geometry and harmonic vibrational frequencies of metanil yellow were calculated by DFT-B3LYP method with LANL2DZ basis set. The vibrational assignments were performed on the basis of the potential energy distribution (PED) of the vibrational modes. Infrared spectra and Bulk Raman spectra were also obtained and characteristic peaks for the title compound were studied. The nonlinear optical properties of the title compound were calculated and discussed. Dipole moment, polarizability and first-order hyperpolarizability of the title compound were reported in order to study nonlinear optical properties (NLO). HOMO-LUMO energy levels were also computed in order to get the bandgap energy. Global reactivity descriptors were calculated using the HOMO and LUMO to predict compound reactivity. UV–Vis spectrum of the title compound was calculated using TD–DFT method. The molecular orbital contributions were studied by density of states (DOSs). Mulliken atomic charges and atomic polar tensors (APT) on each atom were tabulated. A discussion of the vibrational energy of each mode is also presented in this article.